143k views
1 vote
Find dy/dx implicit differentiation of each equation and evaluate at the given point to find the slope at that point.

(x+y)3=x3+y3 at (-1,1)

User Wesleyy
by
4.4k points

1 Answer

7 votes


(x+y)^3=x^3+y^3

Differentiate both sides with respect to
x. By the power and chain rules, we have


(\mathrm d(x+y)^3)/(\mathrm dx)=(\mathrm d(x^3+y^3))/(\mathrm dx)


3(x+y)^2(\mathrm d(x+y))/(\mathrm dx)=3x^2+3y^2(\mathrm dy)/(\mathrm dx)


3(x+y)^2\left(1+(\mathrm dy)/(\mathrm dx)\right)=3x^2+3y^2(\mathrm dy)/(\mathrm dx)

Solve for
(\mathrm dy)/(\mathrm dx):


(3(x+y)^2-3y^2)(\mathrm dy)/(\mathrm dx)=3x^2-3(x+y)^2


(\mathrm dy)/(\mathrm dx)=(3x^2-3(x+y)^2)/(3(x+y)^2-3y^2)


(\mathrm dy)/(\mathrm dx)=(x^2-(x+y)^2)/((x+y)^2-y^2)

At the point (-1, 1), the slope of the tangent line to the curve is


(\mathrm dy)/(\mathrm dx)=((-1)^2-(-1+1)^2)/((-1+1)^2-1^2)=-1

User Sunilda
by
5.3k points